Analisis Struktur Gedung Bertingkat Dengan Menggunakan Metode Statik Ekuivalen dan Dinamik Time History (Studi Kasus: Gedung Telecommunication Telkomsel Center Makasar 2 Sulawesi Selatan) - Daeli, Beta Sabar; Basid, Abdul; Agustine, Dine (JURNAL ILMIAH FAKULTAS TEKNIK, 2024)
Indonesia is a country prone to earthquakes. The high earthquake-prone level is due to the meeting of the plates. The occurrence of this earthquake has proven that there are still many buildings, especially building structures that suffer light to heavy damage and even collapse. This study was conducted to analyze the differences in loading on the building structure using the equivalent static method and dynamic time history at the Telecommunication Telkomsel Center (TTC) building in Makassar 2, South Sulawesi. This study is intended to determine the safety of an earthquake-resistant building structure using the ETABS V.16 program. Classification of moderate soil sites and using concrete quality used fc' = 35 MPa based on SNI 1726 2019. The results show that the calculation of earthquake loading that occurs in building structures using equivalent static analysis is considered accurate because it produces earthquake loading that is close to the results of dynamic analysis calculations. time history. The results of calculations and loading carried out are obtained that the building structure is more stable due to the value of _max. = 0.003991221 0.090909091 building stability due to earthquake direction X and 0.00547442 0.090909091 building stability due to earthquake Y direction so the value of is smaller or does not exceed the value of max in accordance with the provisions of SNI 1726-2019